Comparing ‘Religion’ and ‘Nonreligion’: towards a Critique of Modernity - Horii, Mitsutoshi (Method & theory in the study of religion, 2020)
This essay starts with reference to “grapefruits” in Oliver Freiberger’s (2019) Considering Comparison and to “apples” and “oranges” in Bruce Lincoln’s (2018) Apples and Oranges: Explorations In, On and With Comparison. It disagrees with Freiberger when he compares “grapefruits” with some generic categories in Religious Studies including “shrine.” The category of “shrine” resembles more “fruits,” for example, because two shrines could have completely different genealogies, just like apples and oranges, but still belong to the same generic category. Then, the essay compares the categories of “religion” and “tree.” The boundary between “religion” and “nonreligion” is as arbitrary as that of “tree” and “non-tree.” At the same time, “religion” and “nonreligion” share common characteristics just like “tree” and “non-tree” do. Given this, it concludes with the suggestion that, when the “religiousness” of ostensibly “nonreligious” modernity is articulated, the category “religion” functions as a useful rhetorical tool to subvert modernity’s claim of universality and factual reality.